Who gets all the PIE? Regulation of the statutory audit for private UK companies. Issue 5 (8th August 2019) - Clacher, Iain; Duboisée de Ricquebourg, Alan; May, Amy
Abstract : Purpose: While recently introduced EU regulation on the statutory audit of public interest entities (PIEs) aims to improve audit competition and quality, its success and impact depends on the definition of a PIE applied across the various EU Member States. In the UK, even though little is known about their auditing choices, these changes will not apply to most private companies despite their importance to the wider economy. The purpose of this paper is to provide an in-depth analysis of the private company audit market and examine the lobbying behaviour of the accounting profession around the definition of a PIE in the UK. Design/methodology/approach: Using a large panel of independent private company audits in the UK and a textual analysis of submitted comment letters to a government consultation on the new regulation, this paper presents a comprehensive analysis of the audit market for private companies by measuring supplier concentration using four different measures of market share, and of the lobbying behaviour of the accounting profession. Findings: There are two main findings. First, the private company audit market is characterised by low auditor switching rates along with a tight oligopoly of the largest independent private company audits maintained by the Big Four audit firms. Second, the lobbying behaviour of accounting and audit firms sought, and succeeded, to limit the scope of the definition of a PIE in the UK, consistent with the theoretical predictions of monopoly capitalism and the theory of professions. Originality/value: The paper shows that the definition and scope of a PIE needs revisiting both within the UK and across all EU Member States, with a view to including more of these economically important private companies and highlights the policy challenge of increasing competition and choice in a concentrated audit market.